Illocutionary influence as the criterion of literary translation authenticity - Yessentemirova А.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article is devoted to the study of literary translation in the aspect of rhetorical communication, literary translation authenticity as a factor of communicative efficiency. Semiotic and discourse approaches were applied for the development of the basis of literary translation rhetoric. Such approach con-tributes to the reconstruction of the rhetorical consciousness of the subjects of rhetorical communication. The analysis of the author’s illocutionary influence on the reader was carried out by comparing R. Burns’ ballad and translations by V. Zhukovsky, E. Bagritsky and S. Marshak. The differences of the illocutionary in-fluence in translations, as the base of national and literary identities are explained by the manner of building the Alien and transforming the Alien into the Own. The reason for the differences in the rhetorical consciousness of the subjects of com-munication is justified by the correlation of referential, creative and receptive competencies. The connection of the mentioned text competencies and means of illocutionary influence on the reader, addresses’ portrait and genre structure of the text is testified.